The evaluating of efficacy of McKenzie exercises, Massage and foot Reflexology on pain and disability of men with mechanical chronic low back pain - Sanadgol, Roozbeh; Atri, Ahmad Ebrahimi; Javaheri, Seyd Ali Akbar Hashemi (Ciência e Natura, 2015)
Chronic low-back pain (CLBP) affects most people at some point in their lives. The aim of this study was to evaluate the efficiency of 3 methods which are popular and known as non-invasive way in rehabilitation of CLBP. 60 men in age of group 25-45 with CLBP were randomly divided into four groups (McKenzie, massage, reflexology and control) and instructed to perform McKenzie exercise for 8 week, massage and foot reflexology for 10 days. Patient were assessed by McGill pain questioner (MPQ) and Oswestry Disability Index (ODI), based on pain feeling and the ability to do routine activity of life before starting the study (Pre-test Data) and at the end of study procedure (post-test Data). Results were analyzed by Paired T test, one way ANOVA and Tukey post hock. There was no significantly difference in Pre-treatment session between the 4 groups. MPQ and ODI were significantly lower in post-treatment sessions as compared to pre-treatment values in experimental groups (McKenzie, massage and foot reflexology). Significant decrease in MPQ and ODI values were found in all experimental groups, but no difference in efficacy were found between these groups. However the result that reach from comparison between each of experimental group and control group, showed that the experimental groups were significantly effective. McKenzie exercise, massage and foot reflexology in men with mechanical chronic low-back pain reduce pain and improved disability. Researchers were not found any differences between these 3 methods as compare with each other. Due to the results, Authors suggest that may be using massage therapy or foot reflexology, for patients with CLBP, is better and more effective if therapists are looking for treating in shortest possible duration.